District leadership strategies and its challenges in supporting teaching and learning: perspectives of two districts in South Africa - Mthembu, Pinkie Euginia; Bhengu, Thamsanqa Thulani (Frontiers in Education, 2025)
PurposeEducation districts are critical to providing and sustaining quality teaching and learning. This paper examines the nature of support provided by district officials in two education districts in South Africa (SA) and the challenges encountered in improving quality teaching and learning.MethodologyUnderpinned by the interpretive paradigm and a qualitative research approach, this study employed purposive sampling to select the two districts, with further input from District Directors in identifying additional participants, including Circuit Managers and Curriculum Support officials. Semi-structured interviews served as the data generation technique, and the data were thematically analysed.FindingsThe findings show that while organisational structures are crucial for enhancing efficiency in delivering on mandates, the work of the District Offices in this study did not align with expectations. It is evident that a culture of working in silos and a failure to coordinate activities within districts persisted, thus undermining the noble intentions of policy regulations governing the work of district offices and supporting effective teaching and learning in schools. The participants viewed leadership strategies that neglected lower grades and prioritised Grade 12 as a leadership challenge. Drawing from the findings, we can conclude that the district’s implementation of adequate support for schools remains a challenge.Unique contribution to theory, policy and practiceThis research has brought to the fore a discourse and recognition in the South African context of the need to move away from a compliance-driven accountability paradigm to a support-focused model, and that such a move is a feasible and viable proposition. Therefore, we contribute to the emerging research on district leadership in South Africa by suggesting that enhanced district support could lead to a more inclusive and coherent approach within the district and across schools.